ANALISIS PERFORMA KINERJA COOLING TOWER INDUCED DRAFT COUNTER FLOW DENGAN BAHAN PENGISI ROTAN - Alvin Ulil Amriansyah; Digdo Listyadi Setyawan; Rika Dwi Hidayatul Qoryah (Jurusan Teknik Mesin, 2022)
Cooling tower is defined as a heat exchanger whose working fluid is water and air which functions to cool water by direct contact with air To produce maximum performance from the cooling tower , a filler material is needed which functions to inhibit the flow of water. Rattan has smooth and strong properties against various conditions and is easy to make the desired shape. Previous research on cooling towers has shown that the work performance cooling tower is maximized by using fillers, one of which is using fiber, bamboo and aluminum as fillers.This cooling tower uses 3 layers of rattan filler with the distance between the fillers being equalized with 3 variations of the distance. In the process of testing the same treatment by varying the initial temperature 50 , 60 , 70 , air velocity 4 m/s, 6m/s, 8 m/s, and the distance between fillers 10 cm, 15 cm, 20 cm. Research on cooling towers with rattan as a filler resulted in higher cooling effectiveness and capacity than cooling towers without using fillers. This is evidenced by the highest effectiveness value on a cooling tower with filler material is 96.94%, while the highest value in the cooling tower without filler is 80.24%. The cooling capacity value in the cooling tower with filler is 11.23 kJ/s , while the highest value in the cooling tower without filler is 9.73 kJ/s. Keywords: Cooling Tower, Rattan, Effectiveness